Simulation Case: Hanging/Cardiac Arrest - Lauren Conlon; Nicholas Johnson (Association of American Medical Colleges, 2014)
Abstract Introduction This simulation case was created as part of our Emergency Medicine Resident Simulation Curriculum. The case is based on an actual patient seen in our emergency department and highlights specific teaching points and potential pitfalls in treatment algorithms. The simulation venue offers a unique opportunity to address team dynamics as well as to provide a forum for didactic learning because debriefing a critical case while working in real-time patient care settings is often difficult. Methods The case lasts 15 minutes, with debriefing taking 30-45 minutes. We ran the case consecutively four times in our Simulation Center using Laerdal SimMan. Each case evaluated four to five emergency medicine residents per session, for a total of about 20 residents. In our sessions, a PGY3 resident ran the simulator while a faculty member observed training from inside the simulation room. It is not necessary to have faculty run the simulator or be in the room during the session; however, having faculty assist with debriefing is helpful and beneficial to participants. Results This case has not been used to formally evaluate residents. Information was collected about team dynamics, as well as completion of critical actions, in an effort to target debriefing strategies. Discussion Perhaps in the future we can use simulation to target areas of weakness in participants and tailor education to meet their needs. A limitation of this case is that it has only the initial state programmed and is intended to be run on the fly. This requires the resident, faculty, or technician controlling the mannequin to have knowledge of mannequin operation. While this makes the case more difficult for the instructor, it is more beneficial for participant learning and more realistic.